Odpowiedzi

2010-02-27T21:23:30+01:00
25m-3=24m-4
m=-1 spr -25-3=-24-4

-s+15=4s-14
-5s=1
s=-1/5
i sprawdzenie również wychodzi poprawnie;)
1 2 1
Najlepsza Odpowiedź!
2010-02-27T21:23:52+01:00
A)
25m-3=24m-4 /-24m
1m-3=-4 /+3
m=-1

L=25*(-1)-3=-25-3=-28
P=24*(-1)-4=-24-4=-28
L=P

b)
-s+15=4s-14 /+14
-s+29=4s /+s
29=5s /:5
s=5,8

L=-5,8+15=9,2
P=4*5,8-14=23,2-14=9,2
L=P
2 5 2
2010-02-27T21:26:34+01:00
25m-3=24m-4
25m-24m=-4+3
m=-1
spr. 25x(-1) - 3 =24x(-1) - 4
-25-3=-24-4
-28=-28


-s+15=4s-14
-s-4s=-14-15
-5s=-29 / -5
s=5,8
spr. -5,8 +15=4x 5,8 - 14
9,2=23,2 - 14
9,2=9,2
1 4 1